Activity profile between winners and losers among female exponents in international silat olahraga competition - Pawista, J An; Saphie, Mohamad Nizam Mohamed (Revista de Artes Marciales Asiáticas, 2019)
Aim: The purpose of this study was to determine the details of activity that occurred during the match time between winners and losers among female exponents on Southeast Asian (SEA) Games 2017 silat olahraga competition. Methodology: Twenty female exponents from ten matches (n = 10) of silat olahraga on SEA Games 2017 were selected in this study. The notational analysis focused on fourteen different types of motion categories in silat olahraga: kick, punch, sweep, topple, block, catch, evade/dodge, block and kick, block and punch, block and sweep, fake kick, fake punch, self-release and others. The motion categories were divided into three outcomes, which were Hit Target (HT), Hit Elsewhere (HE) and Missing Opponent (MO). Matched paired t-tests were used to compare differences between winners and losers. Results: There were no significant differences in the activity profiles between winners and losers except for evade/dodge (p = 0.03), but there were significant differences in action outcomes in HT (p = 0.000) and MO (p = 0.025). This study showed that during the match the 51% of the actions were kicks, punches and sweeps. The results also showed that female exponents frequently used lower limbs to attack the opponents. Conclusion: The losers performed less HT actions and higher MO actions compared to the winners. The winners performed more successful actions than the losers during silat matches.